Actualizing the SDGS Through Pesantren Pedagogy: An Iqbalian Panentheistic Foundation for Islamic Educational Philosophy - Rifqi Khairul Anam; Benny Prasetiya; Khoiriyah Khoiriyah; Heri Rifhan Halili; Athar Abdullatif Husain (Sekolah Tinggi Agama Islam Sadra, 2026)
The implementation of the Sustainable Development Goals (SDGs) currently faces a severe motivational crisis due to its reliance on pragmatic-secular frameworks devoid of spiritual grounding. Concurrently, Islamic environmental discourse remains polarized between rigid legalism and passive mysticism. Addressing this gap, this study aims to formulate an Islamic Educational Philosophy by excavating the ecological dimension of the Indonesian pesantren tradition through an Iqbalian panentheistic lens. Employing a qualitative approach grounded in Hans-Georg Gadamer’s philosophical hermeneutics, the research explores a “lived ontology” to achieve a fusion of horizons between historical pesantren pedagogy and contemporary SDG urgencies. The findings reveal a dynamic dialectic of “contextualized panentheism.” This paradigm transitions from a mystical fusion with nature into a proactive ethical stance, embodied by the awakened Iqbal’s concept of khudi as a responsible khalīfah. By perceiving nature as a living divine mirror (tajallī), this pedagogy systematically dismantles the alienated, exploitative Cartesian ego. Empirically, this educational praxis manifests in successful community-driven conservation models—such as the eco-pesantren and customary maritime laws—which consistently outperform secular technocratic policies by internalizing ecological care as a binding moral obligation. The study concludes that pesantren pedagogy provides an authentic, internally driven motivational grammar, ultimately transforming environmental stewardship from an external regulatory duty into a sacred existential expression.